2017
DOI: 10.1038/srep44618
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid suppression of osteocyte perilacunar remodeling is associated with subchondral bone degeneration in osteonecrosis

Abstract: Through a process called perilacunar remodeling, bone-embedded osteocytes dynamically resorb and replace the surrounding perilacunar bone matrix to maintain mineral homeostasis. The vital canalicular networks required for osteocyte nourishment and communication, as well as the exquisitely organized bone extracellular matrix, also depend upon perilacunar remodeling. Nonetheless, many questions remain about the regulation of perilacunar remodeling and its role in skeletal disease. Here, we find that suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
109
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 61 publications
14
109
4
Order By: Relevance
“…A shorter time course or an inducible model would be needed to conclusively address this question. However, our previous studies have shown similar canalicular degeneration within 21 days of glucocorticoid treatment (Fowler et al, 2017) or a week of lactation (unpublished data)(Kaya et al, 2017; Qing et al, 2012; Qing and Bonewald, 2009; Wysolmerski, 2013), thereby indicating that changes in the canalicular network can occur rapidly in a manner that is independent of a maturation defect.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…A shorter time course or an inducible model would be needed to conclusively address this question. However, our previous studies have shown similar canalicular degeneration within 21 days of glucocorticoid treatment (Fowler et al, 2017) or a week of lactation (unpublished data)(Kaya et al, 2017; Qing et al, 2012; Qing and Bonewald, 2009; Wysolmerski, 2013), thereby indicating that changes in the canalicular network can occur rapidly in a manner that is independent of a maturation defect.…”
Section: Discussionmentioning
confidence: 69%
“…This study represents the most definitive evidence so far implicating osteocyte-mediated PLR in the control of bone quality. Previous studies by our group and others show that bone quality is impaired following glucocorticoid treatment or systemic ablation of MMP13, and that PLR is impaired in each case (Fowler et al, 2017; Lane et al, 2006; Tang et al, 2012). Here we find that osteocyte-specific deletion of TGFβ signaling caused defects in PLR and in cortical bone mineralization, flexural strength, ECM material properties, and fracture toughness without impacting cortical bone mass.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations